Commodity Price Shocks : Order within Chaos? - Baffes, John (World Bank, Washington, DC, 2021)
The prices of 27 internationally traded commodities are decomposed into transitory and permanent shocks by applying an ideal band-pass filter to monthly data from 1970–2020. The two types of shocks contributed roughly equally to price variations, but with wide heterogeneity. Permanent shocks ac-counted for two-thirds of the variability in agricultural prices but less than 30 percent in energy prices. The transitory shock component revealed three medium-term cycles. The first (from the early 1970s to the mid-1980s) and third (from the early 2000s to 2020 onward) exhibit similar duration and involve almost all commodities, while the second (spanning the 1990s) is mostly applicable to metals, with the notable absence of energy. The permanent shock components differ across commodities, with an up-ward trend for most industrial commodities and downward trend for agriculture. Moreover, the permanent component of commodity prices where investment is irreversible, including energy, metals, and tree crops, exhibits a high degree of nonlinearities, which also coincide with the two post–World War II supercycles. By contrast, the permanent component of annual agricultural prices is linear, reflecting greater flexibility in investment allocation and input use of these commodities. Prices of commodities subjected to widespread policy interventions, such as international commodity agreements, exhibit persistent deviations from linear trends.